The effect of Gynotype and Nutrient Medium on Callus Inductinon from anther culture of local cauliflower Gynotypes (Brassica oleracea var botrytis.L) (Damascus University Journal of agriculture sciences, 2026)
The research was carried out at the Ghouta Research Station of the General Commission for Scientific Agricultural Research / Damascus, and in the Plant Biotechnology Laboratory of the National Commission for Biotechnology - Ministry of Higher Education / Damascus, during the period 2021-2023, with the aim of callus induction from the anther culture of three genotypes of local cauliflower (J-K-D) collected from the Damascus countryside area (Douma, Kafarsouseh, Jdeidet Artouz). The anthers were cultivated using MS nutrient medium plus different concentrations of phytoregulators of 2,4-D oxin (0, 0.3, and, 0.5 mg/L) and cytokinin BAP (0, 1, and 2 mg/L). The results showed significant superiority of the genotype K in the average number of days to start callus stimulation (8.39 days), and in the average number of days to form callus (11.38 days). The MS3 had the lowest average number of days required to initiate callus stimulation (12.19 days), and the lowest average number of days required for callus formation to begin (15.83 days), with significant differences with other media. Genotype J had the highest average number of callus masses formed (10.94 masses) with significant differences with other Genotypes, and MS1 and MS2 gave the highest average number of callus masses (9.92, and 9.33, respectively), with a significant difference with the MS3 medium (6.83 mass). The average rate of callus induction was recorded significantly in genotype J (45.6%) and significant differences with the rest of the genotypes, while the average rate of callus induction was recorded significantly at the mediums MS1 and MS2 (41.3, and 38.9%, respectively) and without significant differences between them, while the callus induction completely failed in the control, and the callus induction from local cauliflower genotypes were low growth and persistence on the media used, There is a variation in color and size, as for the texture of the callus was cohesive and had a desirable granular appearance in all genotypes.
Keywords: Cauliflower; Callus; Anther culture; Plant Growth Regulators